(4/5)^5.x=(4/5)^7 (3x+1)^3=-26

Question

(4/5)^5.x=(4/5)^7
(3x+1)^3=-26

in progress 0
Orla Orla 1 year 2020-11-12T20:27:58+00:00 2 Answers 65 views 0

Answers ( )

    0
    2020-11-12T20:29:04+00:00

    `(4/5)`$^{5}$ .x = `(4/5)`$^{7}$

    ⇒ `x` = `(4/5)`$^{2}$ 

    (3x+1)^3=-27=-3^3

    suy ra 3x +1 =-3

    x = -3/4

    0
    2020-11-12T20:29:30+00:00

    (4/5)^5.x=(4/5)^7

    ⇔ x=(4/5)^7:(4/5)^5

    ⇔ x=(4/5)^2

    ⇔ x= ( 4^2) / (5^2)

    ⇔ x=16/25

    vậy x =16/25

    (3x+1)^3=-27=-3^3

    ⇔ 3x +1 =-3

    ⇔x = -3/4

    vậy x=-3/4

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )